Bakas retrieving the sense of sacramentality in the ordinary - De Mesa, Jose M. (Pasig City Anvil, 2008)
"Catholicism cherishes the sacramental manner of feeling, thinking and acting within the Christian praxis of the Faith. Such sacramental attitude takes the abiding presence of God in history and culture seriously, recognizing its epiphany in human life and acknowledging its diaphany in the world of the ordinary. In this work, married lay theologian Jose M. de Mesa attempts to make sense of the reality of "sacrament" in the Judeo-Christian Tradition within the world feel of the Filipino culture. He first discerns and analyzes constant theological elements present in the Western Churches? cultural expressions of sacramentality. He utilizes these as guide not only to articulate God?s sacramental presence through the Filipino concept of bakas, but also to ensure the fidelity of this local expression to the Tradition."--Back cover.
Introduction -- Past and largely present understanding of sacraments -- Sacrament and sacramentality in context -- Reappropriating sacrament and sacramentality through bakas and pamamakas -- Postscript : theological constants and inculturations of "sacramentality".
Keywords: Sacraments -- Catholic Church; Catholics -- Philippines